The Criminal Offense of Aggravated Theft under Hammurabi’s Code, Law of the Twelve Tables, Albanian Customary Law and Criminal Code of Kosovo - Krasniqi, Fatmire (Journal of History Culture and Art Research, 2019)
The criminal offense of aggravated theft dealt with and listed under the so-called classic criminality continues to be a worrying phenomenon even in the contemporary period and not just for Kosovo's society. Despite the fact that the notion and content of the property as a protective object of the criminal offense of the aggravated theft has changed over time, property values depending on the period of development of the society, have been protective of the criminal offense in question, always adapted to the period in which prohibited acts of the form of criminal offense of aggravated theft have been incriminated as unlawful acts. Nevertheless, this analytical research initially focuses on the investigation of the history of reporting criminal offenses against property and continues with their elaboration in conformity with the Hammurabi's Code and the Law of the Twelve Tables. Among all criminal offenses against property, we will distinguish and examine the criminal offense of aggravated theft defined under Albanian customary law and which was set forth in particular by the rules of the Code of Lekë Dukagjini, Code of Skanderbeg and of the Code of Labëria, whereas the same social issues will be treated additionally in the legal and criminal aspect according to the legal definition of the Criminal Code of the Republic of Kosovo. The research is conducted based on the application of the historical-legal method in particular.